Punishment Weighting for Criminal Acts of Corruption in Indonesia - Syihab, Mahdi Abdullah; Hatta, Muhammad (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Corruption in Indonesia is categorized as an extraordinary crime where an extraordinary measure is needed to give a deterrent effect to the perpetrators.Purposes of the Research: This study aims at analyzing the various penalties contained in the corruption eradication law as a weight in an effort to reduce the number of corruption in Indonesia.Methods of the Research: This type of research is legalistic, doctrinal or normative. The approach used in normative or legalistic research include a concept approach, a statute approach, historical approach, case approach, and comparative approach. However, this study only uses legal approach since it analyzes the severity of punishment for perpetrators of criminal acts of corruption in Indonesia. The provisions used in this research are Law no. 31 of 1999 jo. Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption and other related laws.Results of the Research: The punishments applied in the law range from imprisonment, additional punishment to the death penalty. In addition, the punishment applied in this provision is in the form of punishment for revocation of political rights, dismissal, and impoverishment. Therefore, the Corruption Eradication Commission does not only use the Corruption Eradication Law in applying these punishments, but also Law no.8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering.